2021
DOI: 10.3390/ani11030721
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Neural Networks and a General Discriminant Analysis for Predicting Culling Reasons in Holstein-Friesian Cows Based on First-Lactation Performance Records

Abstract: The aim of the present study was to verify whether artificial neural networks (ANN) may be an effective tool for predicting the culling reasons in cows based on routinely collected first-lactation records. Data on Holstein-Friesian cows culled in Poland between 2017 and 2018 were used in the present study. A general discriminant analysis (GDA) was applied as a reference method for ANN. Considering all predictive performance measures, ANN were the most effective in predicting the culling of cows due to old age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Cows have increased chances of remaining in the herd if they are healthy, reproduce regularly, have functional feet, legs, and udders, and produce enough milk [ 15 ]. Thus, knowledge of the association between various indicators monitored at the individual animal and herd levels with cow lifespans and culling reasons is essential to predict cow longevity and support optimal decisions in herd management [ 31 ]. The survival and cluster analyses performed in the present study showed some similarities between individual culling categories, which may indicate their direct connection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cows have increased chances of remaining in the herd if they are healthy, reproduce regularly, have functional feet, legs, and udders, and produce enough milk [ 15 ]. Thus, knowledge of the association between various indicators monitored at the individual animal and herd levels with cow lifespans and culling reasons is essential to predict cow longevity and support optimal decisions in herd management [ 31 ]. The survival and cluster analyses performed in the present study showed some similarities between individual culling categories, which may indicate their direct connection.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above, the analysis of longevity and survivability of dairy cows in terms of breeding and production aspects has been a top research topic in recent years. Special attention has been paid to the selection of methods precisely determining the relationships among variables [ 28 , 29 , 30 , 31 ]. It appears that survival analysis is one of them.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on Holstein-Friesian cows culled in Poland between 2017 and 2018 it was found that ANN were the most effective in predicting the culling of cows due to old age (99.76-99.88% of correctly classified cases) and 99.24-99.98% due to reproductive problems. It is significant because infertility is one of the conditions that are the most difficult to eliminate in dairy herds (Adamczyk et al 2021).…”
Section: Predicting the Culling Reasons In Cows Based On Routinely Co...mentioning
confidence: 99%
“…According to 11 developed ANN performances, the optimal numbers of neurons in the hidden layer for Fat%, Protein%, Cheese Merit, Fluid Merit, LIV, SCE, HCR, CCR, Daughter Stillbirth, Sire Stillbirth and GL calculation were: 11 to obtain the highest values of r 2 (during the training cycle r 2 for output variables were: 0.951; 0.947; 0.989; 0.985; 0.902; 0.887; 0.676; 0.953; 0.590; 0.647 and 0.444, respectively), Table 1. The obtained ANN model for prediction of output variables (Fat%, Protein%, Cheese Merit, Fluid Merit, LIV, SCE, HCR, CCR, Daughter Stillbirth, Sire Stillbirth, and GL) was complex (276 weights-biases) because of the high nonlinearity of the observed system (MONTGOMERY, 1984;ADAMCZYK et al, 2021).…”
Section: Ann Modelmentioning
confidence: 99%